2016
DOI: 10.1038/ncomms12543
|View full text |Cite
|
Sign up to set email alerts
|

Mass production of two-dimensional oxides by rapid heating of hydrous chlorides

Abstract: Two-dimensional (2D) nanoscale oxides have attracted research interest owing to their electronic, magnetic optical and catalytic properties. If they could be manufactured on a large scale, 2D oxides would be attractive for applications ranging from electronics to energy conversion and storage. Herein, we report facile fabrication of oxide nanosheets by rapid thermal annealing of corresponding hydrous-chloride compounds. By heating CrCl3·6H2O, ZrOCl2·8H2O, AlCl3·6H2O and YCl3·6H2O crystals as precursors, we imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 45 publications
2
65
0
Order By: Relevance
“…Moreover, this method is easy to scale up for relatively large-scale production. [85] Copyright 2016, Nature Publishing Group. It has been reported that graphene can be produced on a scale of hundreds of kilograms by using a liquid-exfoliation method, opening a door to the commercialization of this material.…”
Section: "Top-down" Synthesis Of 2d Metal Oxide Nanosheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this method is easy to scale up for relatively large-scale production. [85] Copyright 2016, Nature Publishing Group. It has been reported that graphene can be produced on a scale of hundreds of kilograms by using a liquid-exfoliation method, opening a door to the commercialization of this material.…”
Section: "Top-down" Synthesis Of 2d Metal Oxide Nanosheetsmentioning
confidence: 99%
“…The second example is a thermal-exfoliation method designed for the mass production of 2D metal oxides that was developed by Zhao et al [85] In this case, a series of 2D oxide nanosheets, including Cr 2 O 3 , ZrO 2 , Al 2 O 3 , and Y 2 O 3 was obtained by heating the corresponding hydrous-chloride salts. During the rapid heating of the hydrous chloride or oxychloride precursors, water in their crystal lattice was removed and the precursors were hydrolyzed with the release of H 2 O and HCl gases, which caused large pressures to drive the effective exfoliation of the layered solid MCl x (M = metal) and the spontaneous formation of M 2 O x nanosheets.…”
Section: "Top-down" Synthesis Of 2d Metal Oxide Nanosheetsmentioning
confidence: 99%
“…At the same time, hydrous‐chloride compounds would be converted to their corresponding hypochlorites through reaction. Thereafter, hypochlorite 2D crystals can be transformed into corresponding oxide 2D crystals by heating treatment . The heating exfoliation methods mentioned above are solid phase peeling or liquid phase exfoliation.…”
Section: Preparation Of 2d Crystal–based Fibersmentioning
confidence: 99%
“…reported a shear exfoliation method for the scalable production of high-quality 2D materials92122. Wu et al 23. also accomplished the mass production of oxide nanosheets by a rapid thermal annealing treatment of the hydrous-chloride compounds.…”
mentioning
confidence: 99%